2013
DOI: 10.1007/s00784-013-1116-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to severe early childhood caries in south-west Germany

Abstract: Parents of newborn children have to receive information about timely start of tooth brushing and adequate use of nursing bottles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
41
2
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 18 publications
7
41
2
5
Order By: Relevance
“…Furthermore, since 1989 the German social security system has to pay for caries preventive measures applied by public health dentists in kindergartens and schools as well as by dentists in their practices. In spite of all these preventive efforts, the prevalence of caries in Germany remains substantial in adults, and even in children a group with high caries experience persists [Bissar et al, 2014;Jordan et al, 2014]. This pattern is common in most developed countries.…”
Section: Doi: 101159/000490951mentioning
confidence: 99%
“…Furthermore, since 1989 the German social security system has to pay for caries preventive measures applied by public health dentists in kindergartens and schools as well as by dentists in their practices. In spite of all these preventive efforts, the prevalence of caries in Germany remains substantial in adults, and even in children a group with high caries experience persists [Bissar et al, 2014;Jordan et al, 2014]. This pattern is common in most developed countries.…”
Section: Doi: 101159/000490951mentioning
confidence: 99%
“…Studies on risk factors for ECC in different populations have reported various results, including an association between ECC and prolonged breast-feeding [17] and inappropriate feeding practices in very young children [18]. The presence of cariogenic organisms [19], frequency of beverage and food consumption [9, 18, 20], oral hygiene status [21, 22], parental education level, family income [18, 19], caregivers’ oral health knowledge [9, 22, 23], maternal anxiety [24], and child temperament [25] have all been shown to play roles in ECC.…”
Section: Introductionmentioning
confidence: 99%
“…[2,4] Although prevalence varies in different parts of the world, ECC is clearly a public health problem in both developing and industrialized countries. [6][7][8][9][10] Caries risk-based prevention has been found to improve quality of life and provide long-term economic gain [11] but also an important health gain. [12] The use of microbiological screening to improve the prediction of caries risk has been used successfully with both clinical and economic benefits in preschool-and older children.…”
Section: Introductionmentioning
confidence: 99%